EVALUATION OF KNOWLEDGE, PRACTICES OF VITAMIN D AND ATTITUDE TOWARDS SUNLIGHT AMONG INDIAN STUDENTS - Arora, Harsh; Dixit, Vivek; Srivastava, Nidhi (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The current study was carried out to assess the knowledge, practice of Vitamin D and attitudes toward sunlight exposure among Indian students. Methods: We conducted a cross-sectional study on students, studying in Amity University, Noida, India. A pre-designed and self-administered questionnaire was given to all students to collect the information regarding their knowledge about Vitamin D. Results: Almost all (99.5%) students had heard of Vitamin D. The majority of students (53.3%) indicated that sunlight as the main source of Vitamin D, however, knowledge in terms of required daily dose and time in the sun were low among students. Despite having awareness regarding the main source of Vitamin D, 64.2% students did not like going in the sun and percentage (%) of female students who disliked being exposed in the sun were significantly higher (71.1% and 51.6%, respectively; p=0.000). Moreover, female students were a frequent user of sunscreen, applied sunscreen in both summer and winter seasons (47.2% females vs. 37% males; p=0.000). No significant associations were found for the factors, associated with the knowledge of Vitamin D such as the use of sunscreen and hours per day outdoor. Conclusion: The findings of this survey show a lack of consistency between knowledge and attitude, negative approach toward sunlight exposure may severely affect the Vitamin D status of young students. Implementing awareness campaigns and future health programs such as a workshop or training at the college level may help in building more awareness and knowledge about the Vitamin D importance. Keywords: Vitamin D, Sun exposure, Knowledge. Â 